About the composition of the nomadic and semi-nomadic population of the Fergana valley during the Kokand Khanate - Kuzikulov , Ikromjon (The Lingua Spectrum, 2025)
The article examines the pastoral population, nomads, and semi-nomads who lived in the Fergana Valley during the Kokand Khanate period. It provides information about their distribution across the valley, the periods and reasons for their migration, as well as their composition and role in the economic and political life of the Kokand Khanate.